The Reinforcement Learning Workshop Learn How to Apply Cutting-Edge Reinforcement Learning Algorithms to a Wide Range of Control Problems - Palmas, Alessandro (Packt Publishing, Limited, 2020)
With the help of practical examples and engaging activities, The Reinforcement Learning Workshop takes you through reinforcement learning's core techniques and frameworks. Following a hands-on approach, it allows you to learn reinforcement learning at your own pace to develop your own intelligent applications with ease.
Description based upon print version of record. - Batch Normalization
Keywords: Reinforcement learning; Algorithms; Apprentissage par renforcement (Intelligence artificielle); Algorithmes; algorithms; Programming & scripting languages: general; Artificial intelligence; Neural networks & fuzzy systems; Computers; Intelligence (AI) & Semantics; Computers; Neural Networks; Computers; Programming Languages; Python